DSM-H as an African-Born Global Framework for Structural Pathology - Nsiangani, Kibavuidi (CEMA-USK, 2025)
The DSM-H (Diagnostic and Statistical Manual of Human Structural Pathologies) proposes a new way to name harms that do not live inside one person’s “mental disorder” but arise from stable patterns of institutional behaviour. It concentrates on structurally anti-human behaviour clusters (SAHBC / O-SAHBC) that generate preventable damage in health, justice, administration and other vital systems. This paper places DSM-H in an African psycho-political lineage (Fanon, Amos Wilson, Kimbangu) and within the broader MEN-D work on linguistic colonisation, epistemic warfare and digital harassment. It argues that DSM-H is a logical next step in that lineage: an African-born, globally usable system that treats structural pathology as something observable and measurable, independent of what institutional actors claim to feel or intend. Whether an institution “means well” comes second. What matters first is the pattern of decisions and their consequences for human lives. We outline the core DSM-H architecture: the Nsiku–Nzola–Bisalu ethical training triad and the MOYO indicators (MOYO-S, a probability scale for life-aligned behaviour, and MOYO-MBI, an index of life deviation and harm). We show how these tools convert African epistemic concepts (Nsiku, Nzola, Bisalu, mbi) into operational metrics. DSM-H starts its testing in the hospital, where structural cruelty cannot hide behind rhetoric, then moves outward to any context where power, reward and identity combine to normalise injury. DSM-H does not depend on voluntary confession by institutions or professionals. Diagnosis proceeds from pattern and consequence, not from declared motive. This avoids the familiar situation where those who benefit from structural harm can block its naming. DSM-H is built as a protective instrument for populations, with Africa as its starting point and any context of oppression as its horizon. Oppressive systems often recycle the same behavioural templates. DSM-H formalises a safeguard against those templates, from an African vantage point.
Keywords: structural pathology; decolonial diagnosis; health equity metrics; decolonial metrics